ANALISIS EFIKASI DIRI DALAM PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI MA DARUL ULUM - Imroatus Sholihah; Zainul Munawwir; Irma Noervadila (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2020)
The purpose of this study is to describe self-efficacy in internal students mathematical problem solving in terms of students' mathematical ability class XI MA Darul Ulum 2019/2020 school year. This type of research is descriptive qualitative. The subjects of this study were 2 students of class XI MA Darul Ulum with different mathematical ability, namely high and fair. Data collection techniques in this study were observation, interviews, tests problem solving, and documentation. Analysis of the data in this study analyzed on each data collection technique. The results of data analysis show that level of self-efficacy in the problem solving of each students are different, on the student with high mathematical ability show high self-efficacy, student with fair mathematical ability show low self-efficacy, but in problem solving of students with fair mathematical ability are better than the students with high mathematical ability.